Invasive meningococcal disease in Malaysia, Philippines, Thailand, and Vietnam: An Asia-Pacific expert group perspective on current epidemiology and vaccination policies - Usa Thisyakorn; Josefina Carlos; Tawee Chotpitayasunondh; Tran M. Dien; Maria Liza A. M. Gonzales; Nguyen T. L. Huong; Zulkifli Ismail; Musa M. Nordin; Anna Lisa T. Ong-Lim; Terapong Tantawichien; Sangita D. Terumalay; Thiem D. Vu; et al. (Taylor & Francis Group, 2022)
Invasive meningococcal disease (IMD) imposes a significant burden on the global community due to its high case fatality rate (4-20%) and the risk of long-term sequelae for one in five survivors. An expert group meeting was held to discuss the epidemiology of IMD and immunization policies in Malaysia, Philippines, Thailand, and Vietnam. Most of these countries do not include meningococcal immunization in their routine vaccination programs, except for high-risk groups such as immunocompromised people and pilgrims. It is difficult to estimate the epidemiology of IMD in the highly diverse Asia-Pacific region, but available evidence indicate serogroup B is increasingly dominant. Disease surveillance systems differ by country. IMD is not a notifiable disease in some of them. Without an adequate surveillance system in the region, the risk and the burden of IMD might well be underestimated. With the availability of new combined meningococcal vaccines and the World Health Organization roadmap to defeat bacterial meningitis by 2030, a better understanding of the epidemiology of IMD in the Asia-Pacific region is needed.